Post-Lie Magnus Expansion and BCH-Recursion - Al-Kaabi, Mahdi J. Hasan; Ebrahimi-Fard, Kurusch; Manchon, Dominique (Symmetry, Integrability and Geometry: Methods and Applications, 2022)
We identify the Baker-Campbell-Hausdorff recursion driven by a weight λ=1 Rota-Baxter operator with the Magnus expansion relative to the post-Lie structure naturally associated with the corresponding Rota-Baxter algebra. Post-Lie Magnus expansion and BCH-recursion are reviewed before the proof of the main result.